2009
DOI: 10.1007/978-3-642-04076-4_4
|View full text |Cite
|
Sign up to set email alerts
|

Haptic Interaction Techniques for Exploring Chart Data

Abstract: Abstract. Haptic data visualization is a growing research area. It conveys information using the sense of touch which can help visually impaired people or be useful when other modalities are not available. However, as haptic devices and virtual worlds exhibit many challenges, the haptic interactions developed are often simple and limited to navigation tasks, preferring other modalities to relay detailed information. One of the principal challenges of navigation with haptic devices alone, particularly single po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…The results highlighted the relevance of providing several exploration techniques to enable users to perceive information from different perspectives. (Paneels, Roberts, & Rodgers, 2009) investigated similar techniques with the aim of helping users acquire an overview of, and also explore, chart data. Results showed that the free exploration strategy combined with the guidance strategy improves understanding of features of complex line graphs.…”
Section: Strategies For Exploration and Target Searchmentioning
confidence: 99%
“…The results highlighted the relevance of providing several exploration techniques to enable users to perceive information from different perspectives. (Paneels, Roberts, & Rodgers, 2009) investigated similar techniques with the aim of helping users acquire an overview of, and also explore, chart data. Results showed that the free exploration strategy combined with the guidance strategy improves understanding of features of complex line graphs.…”
Section: Strategies For Exploration and Target Searchmentioning
confidence: 99%
“…Haptically scanning over the whole display is difficult and often impractical. Franklin and Roberts [36], [110] describe various guided-tour methods to aid the user to haptically understand the context, while Panëels et al [38] demonstrate a toolkit to create various haptic navigation methods. Other researchers have utilized additional modalities to give the user an understanding of context, place and value, often relying on speech and sonification (E.g.…”
Section: Discussionmentioning
confidence: 99%
“…Three different tour metaphors were proposed: a bus tour where the user is taken on a pre-defined route from start to end, a museum tour where the user stops at predefined points and then can investigate locally, and a water skier tour where the user has some freedom to investigate either-side of the predefined tour. Panëels and Roberts [37] and Panëels et al [38] implemented these tour metaphors and conducted a pilot study for the single line case [37]. The number of subjects was too small to consider the results significant, however it is worth noting that users were in favour of the hypothesis that free exploration combined with the guidance-models improves the understanding of the important graph features, especially in the case of complex line graphs.…”
Section: A Line Graphsmentioning
confidence: 99%
“…This scenario's difficulty involved getting the right combination of the Everytime and Switch blocks with the appropriate option, also not presented during the tutorial. Scenario 4 was a simplified version of the scatter plot overview interaction [27]. The first three task scenarios had increasing difficulty and the last one was performed if time allowed.…”
Section: Pilot Studymentioning
confidence: 99%
“…In addition, every time the device's button is pressed, we select the current highlighted object if it is not already selected. In the context of haptic data visualization, scenarios including: guidance metaphors such as the 'Museum Tour', which conveys an overview of a line chart to visually impaired people; and using a repulsive force based on point concentration to convey a 3D overview of scatter plots have been developed using the tool [27]. A simpler example of the 'museum tour' [25], which deals with the movement interaction only, is illustrated in Figure 4.…”
Section: Examplesmentioning
confidence: 99%